Genetic diversity of MHC class II DRB alleles in the marbled polecat, Vormela peregusna, in Bulgaria. Issue 1 (2nd January 2019) - Nishita, Yoshinori; Spassov, Nikolai; Peeva, Stanislava; Raichev, Evgeniy G.; Kaneko, Yayoi; Masuda, Ryuichi
Abstract : The marbled polecat, Vormela peregusna, is a small marten-like mustelid distributed from southeastern Europe to western China. Since the individual numbers of this species have declined, it has been classified as a vulnerable (VU) species in the 2008 IUCN Red List. To better understand the adaptation of V. peregusna, we investigated diversity and selection in the major histocompatibility complex (MHC) class II DRB gene which is reported to be highly polymorphic in many other species. Among 10 V. peregusna individuals from Bulgaria, we detected 9 novel sequences of partial exon 2, including antigen-binding site (ABS) codons, as representatives of DRB allele ( Vope-DRB s). Two of the alleles were detected in all individuals analysed, while the others showed limited geographical distributions. Our results provided evidence for positive selection on ABS codons and recombination break points, contributing to maintaining the diversity of Vope-DRB s. In a Bayesian phylogenetic tree, all Vope-DRB s grouped within the mustelid clade, with three of them in the basal group consisted of alleles from Meles, Martes, and Vormela but no Mustela alleles, and the others in the derived group consisted of alleles diverged relatively late in the various mustelid species. The Vope-DRB s showed trans-species polymorphism within the mustelid clade, suggesting that the DRB genes evolved under long-lasting balancing selection.